Investigation on Restaurant Layout Design - Malekshahi, Armita (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: Expanding the wind mind of pleasure, comfort is court at its edge. Therefore, a successful implemented layout design could be a breaking point. For a restaurant to accommodate both the customers and associates, the layout design should be given a topmost priority. Layout design for any restaurant makes accomplishment of task efficient for both front and back of the house. Categorically, there are five types of restaurants which can be differentiated as Casual dining, family style, fast dining or high end, fast food or quick services and fast casual. Practically all types of restaurants deal with the same design considerations which are lighting design, colure design, sound and acoustic design, heating, cooling and ventilation design, material design, exterior space design and layout design. Thus, in this thesis the subject matter is to understand “what are the important considerations in restaurant layout design?” defining the restaurant spaces and the relationship between them. The outcome will be valuable for restaurant management, interior designers, architects, architecture and interior design students. The layout design in restaurant can be considered in different variation such as proximity of spaces i.e. lobby, dining area, self-service area, kitchen, storage, water closet, mechanical and electrical room, staff room, changing room to each other, size of spaces, functional sequences and relationship between different functions, flow pattern in spaces, direction of functions and designing for disable groups. Therefore, the aim of this study should serve the analysis of layout design, and create a guideline for successful restaurant design. As a result, the analysis was carried out on the layouts of the selected restaurants i.e Califorian Gold, Funky Buddha, Palm House, Temel Reis, D&B which are located in Gazimagusa in North Cyprus. The selected restaurants used as the case study, are the restaurants that have adequate accessibility to her information, while they are having acceptable architectural designs. these restaurants have a capability of serving food to 130-450 people at the same time while its size is between 450-5500 square meter. Because of the constraint of well design restaurants in Gazimagusa, there are a few restaurants that can be chosen in this study, some of these restaurants selected for inspection, according to the principles can count as casual and fine dining restaurants. Nonetheless, the information gathered are used for restaurant history and also for significant factors in restaurant design. For the field study the selected restaurants were analyzed according to the layout design criteria's, which was developed, on the base of literature survey, observations, interview, sketches and photos which are all part of data collection method. Hence these items were had been used to analyzed each restaurant independently thorough the help of graphs, bubble diagrams, charts and pictures. As a result the analysis conducted with having an acceptable design and design problem. The final layout analysis table, illustrates the acceptable percentage design and design problems for each individual space of all stated restaurants one by one. After reaching to the desired percentage of acceptable design and design problems for each particular restaurants space, presented by chart, which gathers all the restaurant illustration according to the individual layout factors. These charts lead to the knowledge of the final layout design which shows the final categorization of the selected restaurant according to the best result. Keywords: Restaurant, Design, Layout design, Design, Organization, Space relationship. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Memnuniyet zihnin bakış açısını genişletir. Bu nedenle düzen ve tasarım başarılı bir hayatın kesişme noktasıdır. Bir restoran için müşteri ve çalışanların ihtiyaçlarını karşılamak ve ağırlamak adına işleyiş şeması, mekan organizasyonu ve tasarımına özen gösterilmelidir. Herhangi bir restoran için düzen, işleyiş şeması ve tasarımı, hem ön tarafta bulunan müşteri, hem de arka tarafta çalışanlar için işlevsel düzeni ve memnuniyeti artırıcı en önemli unsurların başında gelir. Genel olarak restoranları beş sınıfta incelemek mümkündür. Bunlar; aile restoranları, fast-food (çabuk/hızlı yemek) restoranları, üst düzey restoranlar, gündelik restoranlar, gündelik ve çabuk hazırlanan yemek servis eden restoranlardır. Tarzı ne olursa olsun, tüm restoranlar için mimari ve iç mekan tasarımı özellikle akustik, aydınlatma, ısıtma-soğutma ve havalandırma, malzeme ve renk seçimi, mobilya ve organizasyonu büyük önem taşımaktadır. Tüm bu unsurların gerektiği şekilde etkili olması ise işlevsel düzen, mekan organizasyonu ve tasarımına bağlıdır. Tüm bunlar ışığında, bu çalışmanın esas amacı restoranların barındırdığı işlevler ve bunlar arasındaki ilişkileri tanımlamaktır. Elde edilen sonuçlar restaurat işletmecileri, iç mimarlar, mimarlar, mimarlık ve iç mimarlık öğrencileri için değerli olacaktır. Restoran tasarımı, bizi karşılayan lobiden, yemek yenen mekanlara, personel odasından, mutfak ve çeşitli servis mekanlarına kadar birçok işlev grubunu bir arada arındırmaktadır. Bu nedenle, bu tez çalışmasının amacı, işlevsel düzen, bunların tasarımı ve hizmet analizi ile birlikte başarılı bir restoran tasarımı oluşturmak için öncelik edecek bir rehber oluşturmaktır. Bu amaçla oluşturulan etmenler/veriler seçilen restoranlar üzerinde test edilmiştir. Analiz edilen restoranlar Kuzey Kıbrıs, Gazimağusa da yer almaktadırlar. Bunlar; Califorian Gold, Funky Buddha, Palm House, Temel Reis ve D&B Restoranttır. Seçilen restoranlar örnek değerlendirmelerde kullanılmış, işleyiş şeması ve bunların mimari tasarıma etkileri bakımından değerlendirilmiştir. Bu restoranların büyüklüğü ortalama 450-5500 metrekare arasında iken, aynı anda 130-450 kişiye yemek sunabilme özelliğine sahiptirler. Analiz sonucunda elde edilen verilere göre tasarım ve işlevsel düzenden kaynaklanan problemler saptanmıştır. Değerlendirme sonucunda elde edilen bilgiler tablolar aracılığıyla yüzdelik olarak sunulmuştur. Anahtar Kelimeler; Restoran, tasarım, işlev şeması, organizasyon, mekan ilişkisi.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Assist. Prof. Dr. Nazife Özay.
Keywords: Architecture; Restaurants - Design - Architecture; Restaurants - Decoration; Restaurant - Design - Layout Design - Organization - Space Relationship